Holmes Tremor Partially Responsive to Topiramate: A Case Report. (26th June 2018) - Rojas, Natalia González; Cesarini, Martin; Etcheverry, José Luis; Da Prat, Gustavo; Viera Aramburu, Tomás; Gatto, Emilia Mabel
Background: Holmes tremor is a rare symptomatic movement disorder, characterized by a combination of resting, postural, and intention tremor. It is usually caused by lesions in the brainstem, thalamus, and cerebellum. Despite pharmacological advances, its treatment remains a challenge; many medications have been used with various degrees of effectiveness. Stereotactic thalamotomy and deep brain stimulation in the ventralis intermedius nucleus have been effective surgical procedures in cases refractory to medical treatment. Case Report: Here we report a young woman with topiramate-responsive Holmes tremor secondary to a brainstem cavernoma. Discussion: Herein we report a Holmes tremor responsive to Topiramate.